Nuts, anchor, self-locking, floating, single lug, with counterbore, with MJ threads, classifications: 1100 MPa (at ambient temperature)/235°C, 1100 MPa (at ambient temperature)/315°C and 1100 MPa (at ambient temperature)/425°C. Dimensions. (15th February 1999) - British Standards Institution,
No abstract available